Tirtonadi Bus Terminal Services: An Innovation Derailed? - Ferza, Ray; Hamudy, Moh Ilham A; Rifki, M S (Research and Development Agency Ministry of Home Affairs, 2019)
Bus Terminal, as a revenue-producing service entity in the regional government jurisdiction, is expected to contribute to the independence of the region in the form of the Regional Government's Own-Source Revenue (Pendapatan Asli Daerah/PAD). However, the performance of the bus terminal’s levy was less than desirable. Furthermore, due to the change of authority over some type of bus terminals, it no longer able to produce revenue for the Regional Government. The authority to raise levies from the bus terminals motivated the regional government to introduce service innovations for the bus terminals under their jurisdiction. One example of such innovation was Tirtonadi Bus Terminal in Surakarta, Central Java. This study objective was to understand the impact of the terminal services innovations on the improvement of PAD in Surakarta, Central Java. The study used descriptive methods with a qualitative approach. The result of the study showed that the innovation in Tirtonadi Bus Terminal services was in the form of modernization of the bus terminal's facilities. The impact of terminal services innovations on the increase of levy collections was not significant. The impact of the innovations on the improvement of services was mainly on the physical aspect. The innovations increase customer satisfaction; however, the number of passengers tend to be stagnant and even slightly decrease. Some problems also appear in relation to the change of authority over the bus terminal, in the form of transfer of personnel, funding, infrastructures, and documents (personil, pendanaan, sarana/prasarana dan dokumen/P3D). The change of the authority has a positive impact on the management of the bus terminal. To reap the benefit, the bus terminal management should be directed to utilize a Public Private Partnership cooperation (PPP), change the revenue base and adopt the transit-oriented development (TOD) approach.